Wall-eyed bilateral internuclear ophthalmoplegia in posterior circulation stroke-a case report - A., Mary Stephen; P., Jayasri; J., Harigaravelu P. (International Journal of Advances in Medicine, 2021)
Internuclear ophthalmoplegia is characterised by restricted ocular motility in lateral gaze in which the affected eye shows impairment of adduction and it results from damage to medial longitudinal fasciculus (MLF). Wall-eyed bilateral internuclear ophthalmoplegia (WEBINO) is an extremely rare neurological manifestation which has typical signs including primary gaze exotropia, vertical gaze palsy, ptosis, abducting nystagmus. The common and serious etiological factor is cerebrovascular accident involving the vessels supplying MLF and many cases have life threatening associated neurological impairment. In this case report we have discussed about a gentleman who presented with bilateral ptosis, primary gaze exotropia and headache. Patient found to have vertical gaze palsy and abducting nystagmus on examination. Computed tomography (CT) imaging shows infarct in pontine region and CT angiography revealed basilar artery occlusion supplying region of pons with involvement of posterior cerebral artery. Patient treated with antiplatelet and diplopia managed. Patient showed improvement on subsequent follow-up visits.